Innovation the way forward - Abd Razak, Dzulkifli (2009)
INNOVATION is perceived to be the domain of a select few. Lesser mortals are not meant to innovate. It is best left to the technical people to "invent" something that is earthshattering! This is not necessarily so according to the founding president of the Malaysia Invention and Design Society (MINDS) Professor Tan Sri Augustine S.H. Ong (since 1987). Formerly known as Malaysia Inventors' Club (MIC), it had to rename itself to avoid confusion with political party Malaysian Indian Congress, which uses the same acronym.